Age-Related Maintenance of the Autophagy-Lysosomal System Is Dependent on Skeletal Muscle Type. (24th July 2020) - Fernando, Raquel; Castro, José Pedro; Flore, Tanina; Deubel, Stefanie; Grune, Tilman; Ott, Christiane
Abstract : The skeletal muscle plays an important role in maintaining whole-body mechanics, metabolic homeostasis, and interorgan crosstalk. However, during aging, functional and structural changes such as fiber integrity loss and atrophy can occur across different species. A commonly observed hallmark of aged skeletal muscle is the accumulation of oxidatively modified proteins and protein aggregates which point to an imbalance in proteostasis systems such as degradation machineries. Recently, we showed that the ubiquitin-proteasomal system was impaired. Specifically, the proteasomal activity, which was declining in aged M. soleus (SOL) and M. extensor digitorum longus (EDL). Therefore, in order to understand whether another proteolytic system would compensate the decline in proteasomal activity, we aimed to investigate age-related changes in the autophagy-lysosomal system (ALS) in SOL, mostly consisting of slow-twitch fibers, and EDL, mainly composed of fast-twitch fibers, from young (4 months) and old (25 months) C57BL/6JRj mice. Here, we focused on changes in the content of modified proteins and the ALS. Our results show that aged SOL and EDL display high levels of protein modifications, particularly in old SOL. While autophagy machinery appears to be functional, lysosomal activity declines gradually in aged SOL. In contrast, in old EDL, the ALS seems to be affected, demonstrated by an increased level of key autophagy-related proteins, which are known to accumulate when their delivery or degradation is impaired. In fact, lysosomal activity was significantly decreased in old EDL. Results presented herein suggest that the ALS can compensate the high levels of modified proteins in the more oxidative muscle, SOL, while EDL seems to be more prone to ALS age-related alterations.